Expression of Locally Produced Adipokines and Their Receptors during Different Physiological and Reproductive Stages in the Bovine Corpus Luteum - Granit Thaqi; Bajram Berisha; Michael W. Pfaffl (Animals, 2023)
This study aimed to determine the gene expression of different local novel adipokines, such as vaspin, adiponectin, visfatin, and resistin, and their known receptors, namely, heat shock 70 protein 5, adiponectin receptor 1, and adiponectin receptor 2, in the bovine corpus luteum (CL) during different phases of the estrous cycle (on days 1–2, 3–4, 5–7, 8–12, 13–18, >18) and pregnancy (at months 1–2, 3–4, 5–7, >7). The mRNA expression was measured by reverse transcription polymerase chain reaction (RT-qPCR). The mRNA expression levels were normalized to the geometric mean of all three constantly expressed reference genes (cyclophilin A, ubiquitin, ubiquitin C). Our findings suggest that adipokines are expressed and present in all investigated groups, and are specifically up- or downregulated during the estrus cycle and during pregnancy. Vaspin and adiponectin levels were upregulated in the middle and late cycle stages. Resistin was abundant during the CL regression stage and in the first months of pregnancy. The specific expression of adipokine receptors indicates their involvement in the local mechanisms that regulate CL function. Further investigations are required to elucidate the regulative mechanisms underlying the different local effects of adipokines on the ovarian physiology of cows.